Maturity Levels On Interoperability In Local Tax Services In Pekanbaru City - Miftah, Aisyah Nurterra; As'ari, Hasim; Laila, Nur (Department of Public Administration, 2023)
Electronic-Based Government System (SPBE) is a government administration that utilizes information and communication technology to provide services to SPBE users. The implementation of SPBE depends on the interoperability process used between agencies. Given the importance of the interoperability principle that must be owned by every SPBE architecture, the Government should promulgate laws related to interoperability. BAPENDA Pekanbaru City as an agency authorized to collect district / city local taxes in Pekanbaru City continues to make innovations to provide convenience and improve services for taxpayers (WP). The innovation carried out by BAPENDA Pekanbaru City is the provision of integrated services in accordance with Government Regulation Number 12 of 2019 concerning Regional Financial Management by Implementing an Electronic-Based Government System. Referring to the regulation, SPBE produces Electronification of Local Government Transactions (ETPD) through the Smart Tax Pekanbaru Application can only be used to pay restaurant tax, entertainment tax, hotel tax, and parking tax. This research method uses a qualitative method, with informants obtained by purposive sampling technique. From the research results, it was found that there are still obstacles to the use of smartphones in gaining access to the application due to server licensing, and software management.